Towards Hydrogen Storage through an Efficient Ruthenium‐Catalyzed Dehydrogenation of Formic Acid. Issue 13 (14th June 2018) - Xin, Zhuo; Zhang, Jiahui; Sordakis, Katerina; Beller, Matthias; Du, Chen‐Xia; Laurenczy, Gabor; Li, Yuehui
Abstract: Hydrogen is of fundamental importance for the construction of modern clean‐energy supply systems. In this context, the catalytic dehydrogenation of formic acid (FA) is a convenient method to generate H2 gas from an easily available liquid. One of the issues associated with current catalytic dehydrogenation systems is insufficient stability. Here, we present a robust and recyclable system for FA dehydrogenation by combining a ruthenium 1, 1, 1‐tris(diphenylphosphinomethyl)ethane complex and aluminum trifluoromethanesulfonate (Al(OTf)3 ). This robust system allows steady H2 production under pressure and recycling for an additional 14 runs without any apparent loss of activity (turnover frequencies up to 1920 h −1, turnover numbers up to 20 000). Notably, the catalyst can also be used for the dehydrogenation of formates and the reverse hydrogenation of bicarbonates and CO2 . Abstract : Dehydrogenation station : An efficient ruthenium 1, 1, 1‐tris(diphenylphosphinomethyl)ethane–aluminum trifluoromethanesulfonate catalytic system is developed for formic acid dehydrogenation with an excellent robustness and activity. This robust system allows steady hydrogen production and recycling for an additional 14 runs without any apparent loss of activity at high turnover frequencies and turnover numbers.